Sistemas de manejo e atributos físico-hídricos de um Latossolo Vermelho cultivado com milho - Rossetti, Karina de V. [UNESP]; Centurion, José F. [UNESP] (FapUNIFESP (SciELO), 2013)
The purpose of this experiment was to evaluate the hydro-physical attributes of the Red Oxisol cultivated with maize in Jaboticabal, São Paulo State, Brazil, under different systems of use and periods of adoption of managements. The experiment was arranged in a completely randomized design with split-plot arrangement, with six replications and the treatments were: six years of no-tillage system (SPD6), eight years of no-tillage system (SPD8), ten years of no-tillage system (SPD10), conventional tillage system (SPC) and an adjacent area of native forest (NF). The soil penetration resistance (PR), density, macroporosity, microporosity of the soil in layers of 0-0.05; 0.05-0.10 and 0.10-0.20 m, and the saturated hydraulic conductivity (Kθ) in 0.15 m depth were evaluated. It was found that the PR conditions were favorable for the cultivation to 0.20 m, indicating a structure preserved even after soil chiseling. Furthermore, the Kθ in the soil showed similar behavior between SPC and periods of SPD, although this was shown in a part of maize cycle, macroporosity values near 0.10 m3 m-3 and soil water tensions near 0.09 MPa.
Tillage systems and hydro-physical attributes of an Oxisol cultivated with maize
Keywords: Resistance to penetration; Soil aeration; Zea mays